Associations of breakfast cereal consumption with all-cause and cause-specific mortality: a large-scale prospective analysis - Zhengjun Lin; Min Zeng; Zijian Sui; Yanlin Wu; Hong Zhang; Tang Liu (Nutrition Journal)
Abstract Background Previous studies have explored the relationship between breakfast cereal consumption and mortality risk, but these studies reported inconsistent findings and did not distinguish between consumers of different breakfast cereal types. This prospective cohort study aims to elucidate the dose-response relationship between specific breakfast cereal types and mortality risk. Methods A total of 186,168 participants aged 40 to 69 years from UK Biobank that completed at least one online 24-hour dietary recall questionnaire and reported information on breakfast cereal consumption were included. Self-reported types and amounts of dietary breakfast cereal intake, and mortality from CVD (cardiovascular disease), cancer, and all causes were estimated. Cox regression analyses were employed to illustrate the correlation between the daily intake of different breakfast cereal types and mortality risk. Results During a median follow-up of 13.4 years, 9402 deaths were recorded (including 5073 cancer deaths and 1687 CVD deaths). The intake of muesli was significantly correlated with reduced all-cause mortality, with the HRs (hazard ratios) (95% CIs) being 0.89 (0.83–0.95) (> 0-0.5 bowls/d) and 0.85 (0.79–0.92) (> 0.5-1 bowls/d), respectively. Bran cereal consumption also exhibited inverse correlations with all-cause mortality, showing an HR of 0.88 (95% CI: 0.81–0.95) (> 0-0.5 bowls/d) and 0.88 (95% CI: 0.80–0.98) (> 0.5-1 bowls/d). Moderate intake of porridge (> 0.5-1 bowls/day) was correlated with a reduced risk of all-cause mortality, with an HR (95% CI) of 0.89 (0.84–0.96). Furthermore, moderate consumption of muesli and bran cereal correlated with reduced mortality risks related to CVD and cancer, while plain cereal intake was correlated with increased CVD-specific mortality risk, and sweetened cereal consumption was correlated with elevated cancer-specific mortality risk. Additionally, participants who reported adding dried fruit to their breakfast cereals exhibited significantly lower risks of all-cause mortality and cause-specific mortality, and those who added milk to their breakfast cereals had a reduced risk of all-cause mortality. Conclusions The findings support the moderate intake of several breakfast cereal types, including porridge, bran cereal, and muesli, as part of a healthy diet, while oat crunch and sweetened cereal consumption should be reduced to lower premature mortality risk.